Phthalate Exposure and Neurotoxicity in Children: A Systematic Review and Meta-analysis - Evangelia E. Antoniou; Rainer Otter (Frontiers Media S.A., 2024)
Objectives: This systematic review aims to assess the relationship between prenatal and childhood exposure to phthalates and neurodevelopmental outcomes, identifying periods of heightened susceptibility. Data sources considered studies examining repeated phthalate exposure during pregnancy and childhood on neurodevelopment.Methods: Evaluation included bias risk and study quality criteria. Evidence was synthesized by groups of low and high phthalate molecular weight and exposure measured prenatally and postnatally and outcome measured in childhood. Beta coefficients and their standard errors were extracted, leading to meta-analyses of various neurodevelopmental outcomes: cognition, motor skills, language, behavior, and temperament.Results: Eleven pregnancy and birth cohort studies were identified as relevant. For each phthalate group and outcome combination, there was low or very low evidence of an association, except for prenatal and postnatal phthalate exposure and behavioral development and postnatal exposure and cognition.Conclusion: The estimated effects sizes were relatively small and strong evidence for periods of heightened susceptibility could not be elucidated. No distinction between phthalates of low molecular weight and those of high molecular weight with regards to the outcomes was found.